(untitled) (Nigerian Journal of Pharmaceutical Research, 2021)
Background: The shoot of Borassus aethiopum is cultivated and consumed in Northern Nigeria. Its starch has been investigated for use in pharmaceutical formulation but have limited studies on its toxicity. Toxicity is the degree to which a substance (a toxin or poison) can harm humans or animals. The plant Borassus aethiopum Mart belongs to the family Aracaceae, commonly known as the African Fan Palm. The shoot of the plant is commonly referred to as “Muruchi” in Hausa and is widely available and edible. Objective: This experimental research was designed to examine the potential toxicity of the starch from the shoot of Borassus aethiopum in acute and subacute studies using Wistar rats. Material and Methods: Fresh shoots of Borassus aethiopum were obtained, washed, peeled and grinded using mechanical grinder. The starch was extracted using water. Acute toxicity was carried out using OECD guideline 425. Healthy rats of both sexes were randomly grouped into four groups of six rats each (n=6) for the 28-days oral toxicity study. Distilled water was administered at the dose of 2ml/kg to group I which served as the control while groups II, III and IV were orally administered the starch from the shoot of Borassus aethiopum at the doses of 300, 600 and 1200 mg/kg daily for 28 days respectively. The animals were sacrificed after 28-days at which the blood samples were collected through cardiac puncture into plain and EDTA-containing tubes for biochemical and haematological analyses respectively. The liver, kidney, heart and spleen were excised, weighed and examined macroscopically. Results: The phytochemical screening reveals the presence of alkaloids, tannins, and carbohydrates. The acute toxicity (LD50) of Borassus aethiopum was found to be greater than 4000 mg/kg body weight. No notable and significant changes in the relative organ weight as well as the levels of the renal and hematological biomarkers when compared with the control. However, there was significant increase in serum aspartate aminotransferase (AST) and serum alanine aminotransferase (ALT). Conclusion: In conclusion, the results of this study indicated that the starch from the shoot of Borassus aethiopum showed some evidence of potential toxicity on the liver but did not affect the renal and haematological parameters.